Is hypoalbuminemia a prognostic risk factor for contrast-induced nephropathy in peritoneal dialysis patients? - Hassan K; Fadi H (Dove Medical Press, 2014)
Kamal Hassan,1,2 Hassan Fadi3 1Faculty of Medicine in the Galilee, Bar-Ilan University, Safed, Israel; 2Peritoneal Dialysis Unit, Galilee Medical Center, Nahariya, Israel; 3Sackler Faculty of Medicine, Tel Aviv University, Tel Aviv, Israel Objective: Residual renal function (RRF) is an important predictor of outcome in peritoneal dialysis (PD) patients. Hypoalbuminemia was found to be an independent risk factor for the development of acute kidney injury. We investigated the possibility of an association between serum albumin levels and the development of iodine contrast media-induced nephropathy (CIN) in PD patients.Methods: A total of 103 PD patients who underwent invasive angiographies with exposure to iodine contrast media (ICM) were reviewed retrospectively. All patients received 0.9% saline intravenously at a rate of 75 mL per hour for 12 hours prior, during, and 12 hours after exposure to ICM. Acetylcysteine was given orally at a dose of 600 mg twice daily, on the day before and on the day of exposure to ICM. The nonionic, low-osmolar contrast agent iopromide was used at a mean dose of 75.0±15.2 mL. The changes in RRF from baseline to 1 week and 4 weeks after exposure to ICM were recorded. Outcomes of patients with serum albumin levels <3.8 g/dL and those with serum albumin levels ≥3.8 g/dL were compared. A reduction >30% in RRF at 7 days after exposure to ICM was considered CIN.Results: CIN developed in 27.2% (28/103) of patients. Of the 103 patients, 59.2% (61) had serum albumin levels <3.8 g/dL. Of those, 37.7% (23/61) developed CIN, compared with 11.9% (5/42) of those with serum albumin levels ≥3.8 g/dL (P=0.004). After adjustment for all tested variables in a logistic regression with a stepwise selection model, serum albumin level at exposure to ICM was found to be the most powerful predictor of the development of CIN (odds ratio =4.5; confidence interval =1.5–13.0; P=0.006).Conclusion: PD patients with serum albumin levels <3.8 g/dL should be monitored carefully when exposed to ICM. Serum albumin level may be considered a potential therapeutic target in the prevention of CIN and preservation of RRF in PD patients. Keywords: peritoneal dialysis, renal function, iodine radio-contrast media, iodine contrast media-induced nephropathy